PROMOSI DIGITAL BERBASIS KOMUNITAS PEMBERDAYAAN MASYARAKAT DI MAKAM WALIULLAH SIMBAH BUYUT NDUKOH DI TENGGER WETAN - Sriah, Fendi Prasetyo Utomo; Rofiah, Ulya Ainur; Amin, Syafi'ul; Rofi'udin, Muhammad; Aisyah, Vivi Nur; Ariyanti, Arlina Felisa (CV. Kalimasada Group, 2025)
This community service activity focuses on efforts to empower the residents of Tengger Wetan Village, Tuban, through assistance in digital promotion based on local wisdom, especially related to the preservation of the Tomb of Waliullah Simbah Buyut Ndukoh. The mentoring process is carried out using the ABCD (Asset Based Community Development) method which emphasizes exploring the potential, assets, and strengths of the community to then be developed independently. This approach is realized through a series of participatory activities, ranging from visual and narrative content production training, social media management, to the formation of community-based digital promotion teams. The results of the activity show that the community, especially the younger generation, not only acquires technical skills, but also a deep understanding of religious and cultural values that must be maintained in the delivery of digital messages. Digital promotion was then mutually agreed upon as a means of cultural da'wah, not just a tourism promotion medium. Thus, the application of the ABCD method has been proven to be able to integrate spiritual values, local identity, and modern technology, while strengthening community independence in managing the sustainability of digital promotion in a creative, polite, and educational manner.